Effects of Socioeconomic Factors on Teachers Psychological Wellbeing at University Level - Saima Latif; Dr. Saima Kayani; Misbah Saba (Indus Journal of Social Sciences, 2025)
This study examined the effects of socioeconomic factors on the psychological well-being of university teachers. The objectives were to identify key socioeconomic factors, assess teachers’ psychological well-being, and determine the impact of these factors. A descriptive survey was conducted with 115 teachers from the University of Kotli, AJ&K, selected through simple random sampling. Data were collected using a reliable five-point Likert scale questionnaire and analyzed with SPSS using mean scores, percentages, standard deviations, and correlation. The findings revealed that professional growth, financial benefits, family support, and social recognition positively influenced teachers’ well-being, highlighting the importance of addressing socioeconomic factors to improve mental health and job satisfaction.